Ventilated slabs: Energy consumption mitigation and thermal comfort augmentation - Ozdenefe, Murat; Abokhamis Mousavi, Soad; Atikol, U?ur (Institute of Physics Publishing helen.craven@iop.org, 2019)
This study is an effort to investigate the energy and thermal comfort performance of a ventilated slab application for a particular building type-office building-that is located in Cyprus, which has typical Mediterranean climate with hot dry summers and mild rainy winters. In Cyprus, almost all of the buildings employ reinforced concrete (high thermal mass) for the building frame and slabs. Daytime maximum and night-time minimum temperature difference is substantial, particularly in inland regions of the island during summer time (up to 16 ?C). This traditional building structure together with high diurnal temperature difference generates convenient conditions for the application of ventilated slabs. In this work model of an office building, which is incorporated with ventilated slab is simulated with Energy Plus for the Cyprus weather conditions. The results revealed that the ventilated slab system reduced the cooling energy significantly and augmented the thermal comfort. The variation in the ventilated slab hollows' length and diameter is not effective if the air flow rate is not increased. Thus, the authors suggest to increase the air flow rate through the slab for the best practice. © 2019 IOP Publishing Ltd. All rights reserved.
10th International Conference on Indoor Air Quality, Ventilation and Energy Conservation in Buildings, IAQVEC 2019 -- 2019-09-05 through 2019-09-07 -- Bari -- 153083
Keywords: Air; Air quality; Energy conservation; Energy utilization; Historic preservation; Indoor air pollution; Office buildings; Reinforced concrete; Structural design; Thermal comfort; Ventilation; Best practices; Building frames; Comfort performance; Diurnal temperatures; Mediterranean climates; Minimum temperature differences; Slab applications; Traditional buildings; Zero energy buildings